Identifikasi Karakteristik Hewan Kurban Di Masjid Kompleks Perumahan Wilayah Kota Bogor - Komariah; S. Rahayu; V. A. Mendrofa; S. Priyanto (Jurnal Ilmu Produksi dan Teknologi Hasil Peternakan, 2022)
Eid al-Adha is commemorate by moslems every 10thDzulhijjah with by doing the Eid al-Adha prayer then followed by qurban worship for those who are capable. The aim of this study is to identify characteristics qurban animals at mosque in residential area, Bogor city. The number f qurban animals was 314 heads consisting of 95 heads of cattle, 204 heads of sheep and 15 heads of goats. The research method used was by observing the qurban animals at the research site. The data obtained were then analyzed descriptively. The results showed that the majority of the qurban animals were bali cattle aged ≥ 4 years (33.3%) with a BCS of 4, thin tail sheep aged 2.5-3.0 years (28.9%) with a BCS of 3, Jawarandu goats aged 2.5-3.0 years (37.8%) with a BCS of 4 and the identified qurban animals have met sharia requirements.